2022
DOI: 10.3390/min12040393
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Leaching and Concurrent Cementation of Dissolved Pb and Zn from Zinc Plant Leach Residues

Abstract: Zinc plant leach residues (ZPLRs), particularly those produced using old technologies, have both economic importance as secondary raw materials and have environmental impacts because they contain hazardous heavy metals that pose risks to human health and the environment. Therefore, the extraction and recovery of these metals from ZPLRs has both economic and environmental benefits. In this study, we investigated the removal of lead (Pb) and zinc (Zn) from ZPLRs by alkaline (NaOH) leaching and the concurrent cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Alkaline leaching of metals from concentrate, ores, or waste (mine waste and ewaste) achieves the selective solubilization of amphoteric elements-Al, Pb, Au, and Zn, among others-leaving the iron (Fe), calcium (Ca), and magnesium (Mg) host minerals that may constitute a large percentage of the processed materials. The challenge, however, is that solid-liquid separation by filtration, especially for strong alkaline, is difficult [15]. Silwamba et al [15] investigated the concurrent recovery of dissolved Pb and Zn by cementation on aluminium metal powder from alkaline pulp (i.e., when zinc leach plant residues were leached using NaOH solution) before filtration.…”
Section: Extraction Of Critical Metals By Hydrometallurgy 221 Alkalin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline leaching of metals from concentrate, ores, or waste (mine waste and ewaste) achieves the selective solubilization of amphoteric elements-Al, Pb, Au, and Zn, among others-leaving the iron (Fe), calcium (Ca), and magnesium (Mg) host minerals that may constitute a large percentage of the processed materials. The challenge, however, is that solid-liquid separation by filtration, especially for strong alkaline, is difficult [15]. Silwamba et al [15] investigated the concurrent recovery of dissolved Pb and Zn by cementation on aluminium metal powder from alkaline pulp (i.e., when zinc leach plant residues were leached using NaOH solution) before filtration.…”
Section: Extraction Of Critical Metals By Hydrometallurgy 221 Alkalin...mentioning
confidence: 99%
“…The challenge, however, is that solid-liquid separation by filtration, especially for strong alkaline, is difficult [15]. Silwamba et al [15] investigated the concurrent recovery of dissolved Pb and Zn by cementation on aluminium metal powder from alkaline pulp (i.e., when zinc leach plant residues were leached using NaOH solution) before filtration. The results showed that around 100% of the dissolved Pb was cemented in the leaching pulp when Al metal powder was added.…”
Section: Extraction Of Critical Metals By Hydrometallurgy 221 Alkalin...mentioning
confidence: 99%
“…This is possible since Pb and Zn can both form complexes with hydroxyl ions (OH − ) [ 55 ]. Alkaline leaching presents the advantage of lower dissolution of iron and contamination of the leaching solution [ 56 ]. It also avoids the risk of formation of gel due to the collapse of silicate structures in acidic medium [ 57 ].…”
Section: Recommended Processing Routes For the Recovery Of Valuable M...mentioning
confidence: 99%